A study of human resource training needs for the public libraries in the state of Sarawak/ Mohd Sharif Mohd Saad ... [et al.] - Mohd Saad, Mohd Sharif; Mohamad Norman Masrek, Rusnah Johare; Abdul Rahim, Hasnah; Ismaily, Norlida (2010)
This study was carried out with the objectives of identifying the existing knowledge and skills of the professionals and para-professionals employed by the PUSTAKA Negeri Sarawak and other public libraries in the state of Sarawak (knowledge and skills according to job descriptions and actual daily tasks). In addition, it also sought to identify the actual related knowledge and skills needed by the professionals and para-professionals by comparing their existing knowledge and skills to the existing competencies standards (National Library of Malaysia and the Public Services Department and other best practices standards), and to identify the training needs of the professionals and para-professionals by the PUSTAKA and other public libraries based on the findings. Based on these objectives four hypothesis were formulated namely, the knowledge and skills of the professionals and para-professionals employed by the Sarawak public libraries consists of general competencies; organizational knowledge; library leadership and advocacy; reference and research; collection management; content organization and structure; and library technology management; there will be significant difference between the required competency for the job and the current competency level of the staff in terms of general competencies; organizational knowledge; library leadership and advocacy; reference and research; collection management; content organization and structure; and library technology management; the lower is the current competency level of the staff, the higher is the need for the training; and the higher is the required skill or competency for a given job, the higher is the need for the training. In this study, a mixed-method approach was adopted involving survey research method and structured interviews. Based on the literature, three sets of questionnaires were developed for three categories for job levels i.e Basic for "Penolong Pegawai Perpustakaan", "Pembantu Perpustakaan", and “Pembantu Am Rendah"; Advanced for “Pustakawan" and Expert for "Pustakawan Kanan”. In order to ensure that the developed questionnaires met quality standard, they were piloted with prospective respondents. A total of 576 were sent out to the three categories of respondents but only 525 were returned yielding to 91% response rate. Upon completion of the survey, structured interviews were conducted with selected librarians from several public libraries involving 139 respondents with the purpose of ascertaining the information obtained from the survey and to implore further information. Based on the analyzed data, the results showed that, three out of the four hypotheses were supported. Based on the findings, several recommendations were made. The recommendations are b on the seven areas of competencies namely general competencies, organizational knowledge, library leadership and advocacy, reference and research, collection management, content organization and structure, and library technology management.